A novel internal cold circulation radiofrequency-assisted device for liver transection. (1st January 2021) - Zhou, Yanzhao; Ouyang, Jingzhong; Wang, Zhengzheng; Chen, Xun; Zhu, Ruili; Li, Qingjun; Zhou, Jinxue
Abstract: Purpose: To evaluate the safety and efficacy of a new internal cold circulation bipolar radiofrequency compared with Habib-4X bipolar radiofrequency device in the resection of liver tumors. Methods: A total of 85 patients with hepatocellular carcinoma who received radiofrequency-assisted liver resection from February 2017 to January 2020 were retrospectively enrolled in our study, in which 45 patients received the new internal cold circulation bipolar radiofrequency (New-RF) and 40 patients received Habib-4X bipolar radiofrequency (Habib-4X). Primary outcome measures were the speed of liver transection, the width of coagulation tissue, hemorrhage volume, blood transfusion rate, and operation time. Results: The baseline characteristics of patients in the New-RF and Habib-4X groups had no significant difference ( p  > 0.05). Compared to Habib-4X, the New-RF had a faster average speed of liver transection (4.81 ± 1.20 cm 2 /min vs 3.64 ± 1.08 cm 2 /min, p  < 0.001), a narrower width of coagulation tissue (1.42 ± 0.23 cm 2 vs 1.81 ± 0.20 cm 2, p  < 0.001), a less operation time (55.04 ± 16.12 min vs 64.02 ± 15.09 min, p  = 0.010), a lower rate of needle path bleeding (13.3% vs 35.0%, p  = 0.019), and a lower carbonization rate of electrode needle (22.2% vs 77.8%, p  < 0.001). Hemorrhage during the transection (85.0 ml vs 105.0 ml, p  = 0.438) and hemorrhage per square centimeter (3.28 ± 0.86 ml/cm 2 vs 3.60 ± 1.12 ml/cm 2, p  = 0.141) in the New-RF group were smaller than those in Habib-4X group with no significant difference. Conclusion: The new internal cold circulation bipolar radiofrequency was a safe and efficacious auxiliary device for liver resection with a faster speed of resection, lower carbonization rate of electrode needle, and more precise range of coagulation.